Word-order typology and the acquisition of case marking: A self-paced reading study in Latin as a second language. (July 2019) - VanPatten, Bill; Smith, Megan
This article reports the findings of a study in which we investigated the possible effects of word order on the acquisition of case marking. In linguistic typology (e.g. Greenberg, 1963) a very strong correlation has been shown between dominant SOV (subject object verb) word order and case marking. No such correlation exists for SVO (subject verb object) languages. It is possible then that the mind is more likely to expect case marking when confronted with a language with SOV word order but not necessarily so if the language has SVO word order. We tested this hypothesis with 54 naive learners of Latin with English as a first language (L1). The participants were divided into two groups. One received a 100-word input treatment in Latin that contained only simple SOV sentences, and the other received the same input treatment except that the word order of the treatment sentences was SVO. After the treatment, a surprise self-paced reading test that contained grammatical and ungrammatical case-marked sentences was administered. Participants read test items that matched the word order of the treatment they received (i.e. SOV learners read SOV sentences, and SVO learners read SOV sentences). Results showed a significant slowing down on ungrammatical sentences for the SOV group but not for the SVO group. However, on a test of basic sentence comprehension in which case marking was the cue to determine who did what to whom, we found no distinction between the groups. We discuss these findings in light of how typological universals work in languages and what they could mean for language acquisition.